Harper's illustrated biochemistry: textbook - Rodwell, V. W. Victor W (A LANGE medical book, 2015)
The Thirtieth Edition of Harper's Illustrated Biochemistry combines outstanding full-colorillustrations with authoritative integrated coverage of biochemical disease and clinical information. Using brevity and numerous medically relevant examples, Harper's presents a clear, succinct review of the fundamentals of biochemistry that every student must understand in order to succeed in medical school.